Real-Time IoT-Integrated Ground Control Station (GCS) for Unmanned Aerial Vehicle (UAV) Monitoring System - Lestari, Paramita Eka Wahyu; Ridwan, Mohamad; Ramadhan, Ridzki Fadillah; Nisfa, Faridatun (JEEE-U (Journal of Electrical and Electronic Engineering-UMSIDA), 2025)
Conventional Ground Control Stations (GCS) for UAVs are often platform-bound (PC-only or Android apps), creating installation overhead and constraining mobility. This work introduces a browser-native, web-based GCS that runs across devices without prior installation and ingests MAVLink telemetry from a RadioLink Mini Pix V1.0 flight controller via 433 MHz UART radio telemetry, then streams decoded data to the UI over websocket/JSON. The system visualizes attitude (yaw, pitch, roll/IMU), GPS position and mapping, compass bearing, altitude, and flight status in real time, with user authentication and a structured landing/login flow. In controlled tests, the application delivered stable live visualization and accurate mapping during a 100 m out-and-back flight, with reported coordinates matching the route. Link-budget characterization across 95, 100, 180, 190, and 240 m showed the expected RSSI degradation with distance and a pronounced dip at 190 m, a practical safe range of ~100 m was identified where signal strength stayed >50% with low interference. Compared with PC or Android-based GCS, the proposed approach improves accessibility (zero-install, multi-device) and operational flexibility, while maintaining reliable real-time telemetry for mission monitoring.